Pengaruh Employee Engagement Dan Motivasi Terhadap Kinerja Perawat Dalam Pelaksanaan Pencegahan Dan Pengendalian Infeksi - Anytawati; Dwi Helynarti Syurandhari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Employee engagement refers to the personal involvement of nurses in expressing themselves through their work when carrying out tasks. Engaged and motivated nurses tend to bring innovative ideas, leading to improved performance in the implementation of Infection Prevention and Control. The occurrence of HAIs can diminish the image and quality of hospital services since IPC programs are a key metric for quality control. Therefore, nurses play a crucial role in the implementation of IPC. This research is an analytical correlation study using a cross-sectional method, with proportional sampling techniques involving 103 respondents. Data collection was conducted through questionnaires filled out by the respondents and was subsequently analyzed using Path Analysis with a significance level (?) of 0.05. The Path Analysis results indicate that employee engagement and motivation has a significant impact on nurses' performance in implementing IPC, with a path coefficient of 0.267 and 0.19 and a p-value of 0.000 (p<0.005). The determination coefficient was found to be 0.89. The Path Analysis results show that 89% of the influence on performance can be explained by employee engagement and motivation, while the remaining influence is explained by other factors outside the scope of this study. Management plays a crucial role in enhancing nurses' performance in IPC implementation to improve service quality. Based on the study's findings, it is recommended to improve nurses' competencies through both internal and external training, ensure the availability of adequate facilities and infrastructure, provide regular supervision by IPCN, and offer management support by considering individual, psychological, and organizational factors.